Cost Effective Resource Allocation in C-RAN with Mobile Cloud Computing (International Journal of Engineering and Computer Science, 2017)
To facilitate mobile users service and increase their revenue mobile operators uses Cloud radio access network(C-RAN) and mobile cloud computing(MCC). The aim of this paper is to reduce mobile operator's cost and mobile users task time constraints. Such that we assume the operation happens like the mobile cloud completes the task first and then pass the results back through the C-RAN to users. Considering constraints like user's data rate requirements, maximum transmission power and fronthaul links capacity joint cost-effective resource allocation is proposed between C-RAN and MCC. We solve the optimization problem for resource allocation and admission control of users. Taking the non-linear constraint and solving the problem through big-M method framework. We solve joint cost effective by non-convex optimization with the constraints of task executing time, transmitting power, computation capacity and fronthaul data rates. Using weighted minimum mean square(WMMSE) the non-convex problem is changed to convex problem